Pre-clinical Investigation of Rett Syndrome Using Human Stem Cell-Based Disease Models - Haase, Florencia D.; Coorey, Bronte; Riley, Lisa; Cantrill, Laurence C.; Tam, Patrick P. L.; Gold, Wendy A. (Frontiers in Neuroscience, 2021)
Rett syndrome (RTT) is an X-linked neurodevelopmental disorder, mostly caused by mutations in MECP2. The disorder mainly affects girls and it is associated with severe cognitive and physical disabilities. Modeling RTT in neural and glial cell cultures and brain organoids derived from patient- or mutation-specific human induced pluripotent stem cells (iPSCs) has advanced our understanding of the pathogenesis of RTT, such as disease-causing mechanisms, disease progression, and cellular and molecular pathology enabling the identification of actionable therapeutic targets. Brain organoid models that recapitulate much of the tissue architecture and the complexity of cell types in the developing brain, offer further unprecedented opportunity for elucidating human neural development, without resorting to conventional animal models and the limited resource of human neural tissues. This review focuses on the new knowledge of RTT that has been gleaned from the iPSC-based models as well as limitations of the models and strategies to refine organoid technology in the quest for clinically relevant disease models for RTT and the broader spectrum of neurodevelopmental disorders.